Implementation of LEAD - Part-II: Grants, Competition and Program Operation - Hunter Moorman (Educational Considerations, 1989)
The grants announcement was published in October 1986 and mailed to approximately 3,500 colleges and universities, LEAs, SEAs, education associations, private firms, and individuals. (Development and Implementation of LEAD)